Sengketa Rumah Tangga yang Dipicu Kecanduan Judi Online: Prespektif Hukum Keluarga Islam - Dwiki Alfarisyi Mane Tima; Musleh Harry (Kartika: Jurnal Studi Keislaman, 2025)
The rise of online gambling has become a serious problem that threatens family resilience and contributes to the rising divorce rate in Indonesia. This article aims to analyze online gambling as a reason for divorce, examine the concept of mediation in Islamic family law, and explain its role in addressing divorces caused by online gambling. This study uses a library research method by examining laws and regulations, the Compilation of Islamic Law, Religious Court decisions, and relevant academic studies. The results indicate that: (1) online gambling addiction has a direct impact on family economic instability, neglect of maintenance obligations, recurrent emotional conflict, and psychological violence, thus substantively fulfilling the legal basis for divorce. (2) Mediation in Islamic family law, based on the concept of ishlāḥ, is positioned as a dispute resolution instrument that emphasizes reconciliation and protecting family integrity. (3) In divorce cases caused by online gambling, mediation plays a strategic role in restoring communication, restructuring economic responsibilities, and minimizing the psychological impact on the parties, although its effectiveness depends heavily on the mediator's ability to understand addiction patterns. This article contributes to strengthening mediation's position as a humanistic and transformative legal instrument for addressing family issues in the digital age